2017
DOI: 10.1186/s12944-017-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid increases accumulation of adipocyte triacylglycerol through up-regulation of lipogenic gene expression in pigs

Abstract: BackgroundChanging dietary fatty acid composition in modern diet influences the prevalence of obesity. Increasing evidences suggest favorable effects of n-3 PUFA for protecting against obesity and the metabolic syndrome. However, the regulation of n-3 PUFA in adipose is still unclear. Thus, this study addressed metabolism of different dietary fats in the adipose tissue of porcine model.MethodsEight-week-old cross-bred pigs were randomly assigned to three groups and fed a 2% fat diet for 30 days from either soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long-chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes. 62,63 As previously mentioned, the EP group had elevated level of TGs in the serum. Indeed, an increased deposition of LCFAs in WAT, principally in the form of TGs, can result from increased LCFA synthesis or uptake, augmented conversion of LCFA to TGs, reduced LCFA oxidation, or changes in the TG lipolysis which in turn decreases TG or LCFAs removal.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long-chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes. 62,63 As previously mentioned, the EP group had elevated level of TGs in the serum. Indeed, an increased deposition of LCFAs in WAT, principally in the form of TGs, can result from increased LCFA synthesis or uptake, augmented conversion of LCFA to TGs, reduced LCFA oxidation, or changes in the TG lipolysis which in turn decreases TG or LCFAs removal.…”
Section: Discussionmentioning
confidence: 63%
“…Both SOY and EP diets displayed cellular hypertrophy, compared with the CTRL group, shown as a decrease in the number of adipocytes. It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long‐chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes . As previously mentioned, the EP group had elevated level of TGs in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that potentially upregulated adipogenesis in C2C12 cell culture could be triggered by EPA and DHA treatment. Our findings were consisted with an in vivo study, which showed upregulated adipogenesis in pig suppled with DHA ( 42 ). The upregulated adipogenesis and the decreased myogenic gene expression may indicate that overdosing EPA and DHA is associated with muscle aging.…”
Section: Discussionmentioning
confidence: 72%
“…In literature, polyphenols have been found to influence these genes in different ways by both increasing and decreasing the expression of HSPs [ 16 ]. However, HSPs genes are not only involved in cellular stress response but they also promote muscle development and functionality via myogenesis modulation or by maintaining the structural integrity of the proteins and signaling complexes [ 22 , 64 ]. The two last above-cited pathways were found to be also related to the BP “Monocarboxylic acid biosynthetic process”.…”
Section: Discussionmentioning
confidence: 99%
“…These diet supplementations showed antioxidant and anti-inflammatory activity and positive effects against obesity and insulin-resistance [ 15 19 ]. In pigs, studies on diets supplemented with n -3 PUFA showed that they can influence the expression of genes involved in different biological processes (BPs) such as inflammatory response, fatty acid synthesis and oxidation [ 8 , 9 , 20 22 ], muscle development and differentiation, muscle protein metabolism [ 23 ] and glucose metabolism [ 21 , 24 ]. However, studies on the effects of antioxidants and polyphenols dietary supplementation have been investigated mainly in rodents, and only scarcely in farm animals so far [ 10 , 25 ].…”
Section: Introductionmentioning
confidence: 99%